Composite gel electrolyte for wide-temperature-range lithium battery, lithium battery as well as preparation method and application of composite gel electrolyte
By using a composite gel electrolyte prepared by a dual-solvent solution blending method in a lithium battery, the interaction between lithium polyetheretherketone sulfonate and polyvinylidene fluoride-co-hexafluoropropylene solves the problem of gel electrolytes in a wide temperature range. The problems of low mechanical strength and poor stability have enabled the high-performance operation of lithium batteries in a wide temperature range.
Patent Information
- Application Number
- CN202411311647.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-24
AI Technical Summary
The existing gel electrolytes have low mechanical strength and poor high/low temperature stability in a wide temperature range, resulting in poor electrochemical performance of lithium batteries.
Use dual -solvents solution to prepare composite gel electrolytes, and interact with polyethyl fluoropylol acrylathe in polytatolytic ethylene, and interaction with polytaroninylinylinylene. Mechanical strength and stability.
It improves the mechanical strength and low-temperature/high-temperature stability of the composite gel electrolyte, enhances the lithium ion migration number and ionic conductivity, and enables the lithium battery to have good cycle stability in the temperature range of -20 to 70°C.
Smart Images

Figure CN119361813A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium battery materials, and in particular to a composite gel electrolyte for wide temperature range batteries, a lithium battery, and a preparation method and application thereof. Background Art
[0002] Lithium batteries have attracted widespread attention due to their high energy density. Currently, lithium batteries mainly use liquid electrolytes, which have the advantages of high ion mobility, good chemical stability, high voltage and high specific energy. However, liquid electrolytes have problems such as flammable organic solvents, electrolyte leakage and lithium dendrite growth, which hinder the large-scale application of lithium-ion batteries as energy storage devices. Therefore, gel electrolytes that combine the high safety of solid polymers and the high ionic conductivity of liquid electrolytes have become an ideal choice for the next generation of lithium-ion batteries.
[0003] The performance of gel electrolytes and the interfacial properties of batteries are greatly affected by temperature. At low temperatures, the ionic conductivity of gel electrolytes is low, the interfacial impedance is large, and the battery discharge capacity is low; at high temperatures, the liquid solvent in the gel electrolyte evaporates rapidly and has poor stability, which poses great challenges to the safety and cycle life of lithium batteries. Existing gel electrolytes are difficult to apply to wide-temperature lithium batteries. It is of great significance to improve the applicable temperature range of gel electrolytes so that they have high ionic conductivity in a wide temperature range, good low / high temperature stability, good mechanical strength and other characteristics.
[0004] At present, the applicable temperature range of gel electrolytes is mainly broadened by component regulation (optimizing the combination of salt and solvent, adding functional fillers) and structural design. However, the gel electrolytes prepared by the above methods have problems such as component incompatibility and structural instability, and their mechanical strength and stability are poor, resulting in poor performance of lithium batteries in a wide temperature range. Summary of the invention
[0005] The present application provides a composite gel electrolyte for a wide temperature range lithium battery, a lithium battery, and a preparation method and application thereof, aiming to solve the problem that the existing gel electrolyte has low mechanical strength, poor high / low temperature stability and poor electrochemical performance, which in turn leads to poor electrochemical performance of lithium batteries under a wide temperature range.
[0006] In order to achieve the above objectives, the present application adopts the following technical solutions.
[0007] In a first aspect of the present application, a method for preparing a composite gel electrolyte for a wide temperature range lithium battery is provided, comprising:
[0008] S1, dissolving polyvinylidene fluoride co-hexafluoropropylene in a first organic solvent to obtain a solution A;
[0009] Dispersing lithium polyetheretherketone sulfonate in a second organic solvent and stirring to obtain a solution B;
[0010] S2, mixing solution A and solution B, heating and stirring, pouring them into a mold and vacuum drying them to obtain a composite polymer film;
[0011] S3, immersing the polymer film in an electrolyte until it swells to obtain a composite gel electrolyte.
[0012] Preferably, the polyetheretherketone sulfonate lithium is prepared by the following method:
[0013] Dissolve polyetheretherketone in 98% concentrated sulfuric acid, stir at 60-80°C for 1-5h under nitrogen atmosphere, collect solid phase product, wash to neutrality, and dry to obtain sulfonated polyetheretherketone;
[0014] The sulfonated polyetheretherketone is dispersed in a lithium hydroxide solution, stirred, and dried to obtain polyetheretherketone lithium sulfonate.
[0015] Preferably, the molecular weight of the polyvinylidene fluoride-co-hexafluoropropylene is 200,000-600,000; the molecular weight of the polyetheretherketone lithium sulfonate is 20,000-50,000, and the degree of sulfonation is 50%-95%.
[0016] Preferably, the first organic solvent comprises any one of dichloromethane, chloroform, acetone, butanone or 2-pentanone;
[0017] The second organic solvent includes any one of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide or N,N-dimethylacetamide.
[0018] Preferably, in the solution A, the concentration of polyvinylidene fluoride co-hexafluoropropylene is 0.01 to 0.05 g / ml;
[0019] In the solution B, the concentration of lithium polyetheretherketone sulfonate is 0.004-0.04 g / ml.
[0020] Preferably, in step S2, the heating temperature is 25-60°C; the vacuum drying temperature is 25-100°C.
[0021] Preferably, the solute of the electrolyte is bis(trifluoromethanesulfonyl)imide lithium salt, and the solvent is a mixed solvent of 1,3-dioxolane and ethylene glycol dimethyl ether; the concentration of the electrolyte is 0.8-2 mol / L.
[0022] In a second aspect of the present application, a composite gel electrolyte prepared by the above preparation method is provided.
[0023] The third aspect of the present application provides application of the above composite gel electrolyte in a lithium battery.
[0024] In a fourth aspect of the present application, a lithium battery is provided, comprising a positive electrode, a negative electrode and the above-mentioned composite gel electrolyte; the active material of the positive electrode comprises lithium iron phosphate or a sulfur-carbon composite material, and the active material of the negative electrode comprises lithium metal or a lithium alloy.
[0025] Compared with the prior art, the beneficial effects of this application are:
[0026] The composite gel electrolyte of the present application is prepared by a dual solvent solution blending method, and polyetheretherketone sulfonate lithium and polyvinylidene fluoride co-hexafluoropropylene in its polymer matrix form a suitable nanophase distribution through chain entanglement and ion-dipole interaction, thereby enhancing the mechanical strength and low-temperature / high-temperature stability of the electrolyte; in the composite gel electrolyte, the lithium sulfonate groups anchored on the solvated polymer chains promote the formation of continuous ion channels in the gel electrolyte, so that it has higher ionic conductivity and lithium ion migration number.
[0027] The lithium battery using the composite gel electrolyte provided in the present application has good cycle stability in the temperature range of -20 to 70°C and is suitable for the field of energy storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0029] Figure 1 Atomic force microscope images of the composite gel electrolyte prepared in Example 1 and Comparative Example 1;
[0030] Figure 2 Graphs showing ionic conductivity of the composite gel electrolytes prepared in Example 1 and Comparative Example 1;
[0031] Figure 3 Electrochemical performance diagram of lithium batteries assembled with composite gel electrolytes prepared in Example 1 and Comparative Example 1 at -20°C, 25°C, and 70°C. DETAILED DESCRIPTION
[0032] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0033] In the following description of this embodiment, the terms "include", "comprising", "having" and "containing" are all open terms, meaning including but not limited to.
[0034] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.
[0035] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0036] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0037] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0038] Those skilled in the art will appreciate that the numerical ranges in the embodiments of the present application are to be construed as specifically disclosing each intermediate value between the upper and lower limits of the scope. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present application. The upper and lower limits of these smaller ranges may be independently included or excluded in the scope.
[0039] Unless otherwise specified, the technical / scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which this application belongs. Although this application only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of this application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0040] In a first aspect, the present application provides a method for preparing a composite gel electrolyte for a wide temperature range lithium battery, comprising:
[0041] S1, dissolving polyvinylidene fluoride and hexafluoropropylene in a first organic solvent to obtain a solution A; preferably, the concentration of polyvinylidene fluoride and hexafluoropropylene in the solution A is 0.01 to 0.05 g / ml;
[0042] Disperse lithium polyetheretherketone sulfonate in a second organic solvent and stir to obtain a solution B. Preferably, the concentration of lithium polyetheretherketone sulfonate in solution B is 0.004-0.04 g / ml.
[0043] In the present application, the molecular weight of polyvinylidene fluoride-co-hexafluoropropylene is preferably 200,000-600,000; the molecular weight of polyetheretherketone lithium sulfonate is preferably 20,000-50,000, and the degree of sulfonation is preferably 50%-95%.
[0044] Wherein, polyetheretherketonesulfonate lithium is prepared by the following method:
[0045] Dissolve polyetheretherketone in 98% concentrated sulfuric acid, stir at 60-80°C for 1-5 hours under nitrogen atmosphere, collect solid phase product, wash to neutrality, and dry at 60°C for 24 hours to obtain sulfonated polyetheretherketone;
[0046] The sulfonated polyetheretherketone is dispersed in a lithium hydroxide solution with a concentration of 1 mol / L, stirred for 12 hours, and dried to obtain polyetheretherketone lithium sulfonate.
[0047] In the present application, the first solvent is a good solvent of polyvinylidene fluoride and hexafluoropropylene, and any one of dichloromethane, chloroform, acetone, butanone or 2-pentanone can be selected; the second solvent can be any one of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide or N,N-dimethylacetamide.
[0048] S2, mixing solution A and solution B, heating and stirring, pouring them into a mold and vacuum drying them to obtain a composite polymer film;
[0049] Specifically, solution A and solution B are mixed, stirred evenly at a temperature of 25 to 60° C., poured into a polytetrafluoroethylene mold, and dried at 25 to 100° C. under vacuum to evaporate the solvent, thereby obtaining a composite polymer film.
[0050] S3, immersing the polymer film in an electrolyte until it swells to obtain a composite gel electrolyte.
[0051] Specifically, the solute of the electrolyte is bis(trifluoromethanesulfonyl)imide lithium salt, and the solvent is a mixed solvent of 1,3-dioxolane and ethylene glycol dimethyl ether. In the electrolyte, the concentration of bis(trifluoromethanesulfonyl)imide lithium salt is preferably 0.8-2 mol / L.
[0052] Lithium polyetheretherketone sulfonate and polyvinylidene fluoride co-hexafluoropropylene form a suitable nanophase distribution through polymer chain entanglement and ion-dipole interaction.
[0053] The composite gel electrolyte prepared by the present application adopts a dual solvent solution blending method, wherein lithium polyetheretherketone sulfonate and polyvinylidene fluoride co-hexafluoropropylene form a suitable nanophase distribution through chain entanglement and ion-dipole interaction, which can improve the mechanical strength and low-temperature / high-temperature stability of the electrolyte membrane; at the same time, the lithium sulfonate groups anchored on the solvated polymer chain promote the formation of continuous ion channels in the gel electrolyte, and the electrolyte has a high ionic conductivity and lithium ion migration number. The composite gel electrolyte prepared by the present application has high mechanical strength and good heat resistance, and can be used as an electrolyte for lithium batteries.
[0054] The present application also provides a lithium battery, which includes a positive electrode, a negative electrode and a composite gel electrolyte prepared in the present application. The active material of the positive electrode of the lithium battery is lithium iron phosphate or a sulfur-carbon composite material, and the active material of the negative electrode is lithium metal or a lithium alloy. The lithium battery has good cycle stability in the temperature range of -20 to 70°C and can be used as an energy storage device in the energy storage field.
[0055] The present application is further described below by way of examples. In the examples of the present application, all raw materials and reagents can be obtained by purchasing commercial products, and their purity is analytical grade or above.
[0056] Example
[0057] This embodiment provides a method for preparing lithium polyetheretherketone sulfonate, comprising:
[0058] Dissolve polyetheretherketone in 98% concentrated sulfuric acid, stir at 70°C in a high-purity nitrogen atmosphere, and after stirring for 5 hours, collect the solid phase product by filtration, and wash with ice water until the pH is 6-7. Dry the obtained product at 60°C for 24 hours to obtain sulfonated polyetheretherketone; soak the sulfonated polyetheretherketone in 1 mol / L aluminum hydroxide aqueous solution, stir for 12 hours, and dry to obtain polyetheretherketone lithium sulfonate.
[0059] Example 1
[0060] This embodiment provides a method for preparing a composite gel electrolyte for a wide temperature range lithium battery, comprising:
[0061] S1, adding 0.25 g of polyvinylidene fluoride-co-hexafluoropropylene with a molecular weight of 400,000 into 10 mL of acetone, stirring and dissolving at room temperature to obtain a uniform solution A;
[0062] 0.05 g of lithium polyetheretherketone sulfonate having a molecular weight of 35,000 and a sulfonation degree of 90% was mixed and stirred evenly with 5 mL of N,N-dimethylacetamide to obtain a solution B;
[0063] S2, mixing solutions A and B and stirring at 60°C, then pouring into a polytetrafluoroethylene mold, vacuum drying at 80°C, and obtaining a composite polymer film after the solvent evaporates;
[0064] S3, dissolving lithium bis(trifluoromethanesulfonyl imide) in a mixed solvent of ethylene glycol dimethyl ether and 1,3-dioxolane in a volume ratio of 1:1 to prepare an electrolyte solution with a lithium bis(trifluoromethanesulfonyl imide concentration of 1 mol / L; soaking the composite polymer film in the electrolyte solution for 1 hour, so that the composite polymer film swells and a composite gel electrolyte is obtained. Example 2
[0065] This embodiment provides a method for preparing a composite gel electrolyte for a wide temperature range lithium battery, comprising:
[0066] S1, adding 0.5 g of polyvinylidene fluoride co-hexafluoropropylene with a molecular weight of 200,000 into 10 mL of butanone, stirring and dissolving at room temperature to obtain a uniform solution A;
[0067] 0.025 g of lithium polyetheretherketone sulfonate having a molecular weight of 40,000 and a sulfonation degree of 70% was mixed and stirred evenly with 5 mL of N-methylpyrrolidone to obtain a solution B;
[0068] S2, mixing solutions A and B and stirring at 40°C, then pouring into a polytetrafluoroethylene mold, vacuum drying at 60°C, and obtaining a composite polymer film after the solvent evaporates;
[0069] S3, dissolving lithium bis(trifluoromethanesulfonyl imide) in a mixed solvent of ethylene glycol dimethyl ether and 1,3-dioxolane in a volume ratio of 1:1 to prepare an electrolyte with a lithium bis(trifluoromethanesulfonyl imide concentration of 1.5 mol / L; immersing the composite polymer film in the electrolyte for 1 hour, allowing the composite polymer film to swell, thereby obtaining a composite gel electrolyte.
[0070] Example 3
[0071] This embodiment provides a method for preparing a composite gel electrolyte for a wide temperature range lithium battery, comprising:
[0072] S1, adding 0.3 g of polyvinylidene fluoride-co-hexafluoropropylene with a molecular weight of 400,000 into 10 mL of acetone, stirring and dissolving at room temperature to obtain a uniform solution A;
[0073] 0.1 g of lithium polyetheretherketone sulfonate having a molecular weight of 35,000 and a sulfonation degree of 50% was mixed and stirred evenly with 5 mL of N-methylpyrrolidone to obtain a solution B;
[0074] S2, mixing solutions A and B and stirring at 50°C, then pouring into a polytetrafluoroethylene mold, vacuum drying at 100°C, and obtaining a composite polymer film after the solvent evaporates;
[0075] S3, dissolving lithium bis(trifluoromethanesulfonyl imide) in a mixed solvent of ethylene glycol dimethyl ether and 1,3-dioxolane in a volume ratio of 1:1 to prepare an electrolyte with a lithium bis(trifluoromethanesulfonyl imide concentration of 2 mol / L; immersing the composite polymer film in the electrolyte for 1 hour, allowing the composite polymer film to swell, thereby obtaining a composite gel electrolyte.
[0076] Example 4
[0077] This embodiment provides a method for preparing a composite gel electrolyte for a wide temperature range lithium battery, comprising:
[0078] S1, adding 0.3 g of polyvinylidene fluoride co-hexafluoropropylene with a molecular weight of 600,000 into 10 mL of 2-pentanone, stirring and dissolving at room temperature to obtain a uniform solution A;
[0079] 0.05 g of lithium polyetheretherketone sulfonate having a molecular weight of 50,000 and a sulfonation degree of 95% was mixed and stirred evenly with 5 mL of dimethyl sulfoxide to obtain a solution B;
[0080] S2, mixing solutions A and B and stirring at 50°C, then pouring into a polytetrafluoroethylene mold, vacuum drying at 100°C, and obtaining a composite polymer film after the solvent evaporates;
[0081] S3, dissolving lithium bis(trifluoromethanesulfonyl imide) in a mixed solvent of ethylene glycol dimethyl ether and 1,3-dioxolane in a volume ratio of 1:1 to prepare an electrolyte with a lithium bis(trifluoromethanesulfonyl imide concentration of 1 mol / L; immersing the composite polymer film in the electrolyte for 1 hour, allowing the composite polymer film to swell, thereby obtaining a composite gel electrolyte.
[0082] Comparative Example 1
[0083] The difference between Comparative Example 1 and Example 1 is that no polyetheretherketonesulfonate lithium is added when preparing Solution B, and the rest is the same as Example 1.
[0084] Comparative Example 2
[0085] The difference between Comparative Example 2 and Example 2 is that the lithium polyetheretherketone sulfonate in Example 2 is replaced by sulfonated polyetheretherketone, and the rest is the same as Example 2.
[0086] The phase distribution and Young's modulus of the composite gel electrolyte prepared in Example 1 and Comparative Example 1 were tested. The results are as follows: Figure 1 shown.
[0087] from Figure 1 It can be seen that the composite gel electrolyte prepared in Example 1 has a uniform nanoscale phase distribution, and the average Young's modulus is as high as 3.47GPa; while the composite gel electrolyte prepared in Comparative Example 1 without adding lithium polyetheretherketone sulfonate has obvious phase separation between the crystalline phase and the amorphous phase, and the distribution is uneven, and the average Young's modulus is only 2.34GPa. The above test results show that the nanoscale blending of polyetheretherketone can play the role of a rigid support to maintain the stability of the gel electrolyte, so that the composite gel electrolyte has excellent mechanical properties.
[0088] Stainless steel symmetrical batteries were assembled using the composite gel electrolytes prepared in Example 1 and Comparative Example 1, and electrochemical performance tests were performed. The specific method was as follows: in an anhydrous and oxygen-free glove box, the two gel electrolytes were cut into the size of a button battery separator, and the separator and electrolyte in the button battery were replaced with the two gel electrolytes. Two stainless steel sheets were used as the positive electrode and the negative electrode, respectively, to assemble a button stainless steel symmetrical battery.
[0089] The electrochemical performance of the stainless steel symmetrical battery assembled with the composite gel electrolyte of Example 1 and the stainless steel symmetrical battery assembled with the composite gel electrolyte of Comparative Example 1 was tested at 25° C. using an electrochemical workstation (CHI760E). The test results are as follows: Figure 2 shown.
[0090] Depend on Figure 2 It can be seen that the ionic conductivity of the composite gel electrolyte of Example 1 is 2×10 -3 S cm -1 , the lithium ion migration number is 0.59; the ionic conductivity of the composite gel electrolyte of Comparative Example 1 is 1×10 -3 S cm -1 , and the lithium ion migration number is 0.32. The ionic conductivity and lithium ion migration number of the composite gel electrolyte of Example 1 are better than those of the composite gel electrolyte of Comparative Example 1, which proves that the addition of lithium polyetheretherketonesulfonate can optimize the polymer chain solvation structure in the composite gel electrolyte and form a continuous ion transport phase, thereby significantly improving the ionic conductivity.
[0091] In the same manner, the composite gel electrolytes prepared in Example 2 and Comparative Example 2 were assembled into a stainless steel stack battery and tested. The ionic conductivity of the composite gel electrolyte in Example 2 with the addition of lithium polyetheretherketone sulfonate was 2.3×10 -3 Scm -1 , which is higher than the ionic conductivity of the composite gel electrolyte in comparative example 2 with sulfonated polyetheretherketone added by 1.4×10 -3 S cm -1 , indicating that lithium sulfonate anchored on the polymer enhances the ion transport capacity of the composite gel electrolyte.
[0092] Lithium batteries were assembled using the composite gel electrolytes prepared in Example 1 and Comparative Example 1, and electrochemical performance tests were performed. The specific method was as follows: in an anhydrous and oxygen-free glove box, a lithium metal sheet was used as the negative electrode, a lithium iron phosphate electrode sheet was used as the positive electrode, and a lithium battery was assembled using the composite gel electrolyte.
[0093] The lithium battery assembled with the composite gel electrolyte of Example 1 and the lithium battery assembled with the composite gel electrolyte of Comparative Example 1 were tested for their electrochemical performance on a LAND test system at temperatures of -20°C, 25°C and 70°C. The test results are shown in Figure 3 shown.
[0094] Figure 3 a is the charge and discharge curve of the lithium battery assembled in Example 1 and Comparative Example 1 at -20°C and 0.2C rate. The lithium battery assembled in Example 1 has a discharge capacity of 85 mAh g -1 , which is higher than the discharge capacity of comparative example 1 by 55 mAh g -1 , indicating that the low-temperature performance of the composite gel electrolyte of the present application is significantly improved.
[0095] Figure 3 b is a test diagram of the cycle performance of the lithium battery assembled in Example 1 and Comparative Example 1 at 25°C and 5C rate. The discharge capacity of the lithium battery assembled in Example 1 is 121 mAh g -1 The capacity of the comparative example 1 was 106 mAh g -1 After 104 cycles, the battery was damaged by internal short circuit.
[0096] Figure 3 Figure c is a test diagram of the cycle performance of the lithium batteries assembled in Example 1 and Comparative Example 1 at 70°C and 2C rate. The lithium battery assembled in Example 1 exhibits a higher discharge specific capacity and a more stable cycle performance, while the capacity of the lithium battery assembled in Comparative Example 1 decays significantly.
[0097] Depend on Figure 3The test results show that the composite gel electrolyte prepared in the present application has good stability at both high and low temperatures, and the lithium battery assembled therefrom has good cycle stability in the temperature range of -20 to 70°C, and is suitable for the field of energy storage.
[0098] In the same manner, the composite gel electrolytes prepared in Example 2 and Comparative Example 2 were assembled into lithium batteries and tested. The test results show that the lithium battery assembled in Example 2 maintains a stable capacity at -20°C, 25°C and 70°C, which is significantly better than the lithium battery assembled in Comparative Example 2, indicating that lithium sulfonate anchored on the polymer can effectively improve the cycle performance and battery life of lithium batteries under wide temperature range conditions.
[0099] The composite gel electrolytes prepared in Examples 3 and 4 have comparable performance to the composite gel electrolyte prepared in Example 1 after testing.
[0100] Although the present application has been described in detail in general terms and in specific embodiments in this specification, it is obvious to those skilled in the art that some modifications or improvements may be made to the present application. Therefore, these modifications or improvements made without departing from the spirit of the present application are within the scope of protection claimed in the present application.
Claims
1. A method for preparing a composite gel electrolyte for a wide temperature range lithium battery, characterized in that: include: S1, dissolving polyvinylidene fluoride co-hexafluoropropylene in a first organic solvent to obtain a solution A; Dispersing lithium polyetheretherketone sulfonate in a second organic solvent and stirring to obtain a solution B; S2, mixing solution A and solution B, heating and stirring, pouring them into a mold and vacuum drying them to obtain a composite polymer film; S3, immersing the polymer film in an electrolyte until it swells to obtain a composite gel electrolyte.
2. The preparation method according to claim 1, characterized in that: The polyetheretherketone sulfonate lithium is prepared by the following method: Dissolve polyetheretherketone in 98% concentrated sulfuric acid, stir at 60-80°C for 1-5h under nitrogen atmosphere, collect solid phase product, wash to neutrality, and dry to obtain sulfonated polyetheretherketone; The sulfonated polyetheretherketone is dispersed in a lithium hydroxide solution, stirred, and dried to obtain polyetheretherketone lithium sulfonate.
3. The preparation method according to claim 1, characterized in that: The molecular weight of the polyvinylidene fluoride-co-hexafluoropropylene is 200,000-600,000; the molecular weight of the polyetheretherketone lithium sulfonate is 20,000-50,000, and the sulfonation degree is 50%-95%.
4. The preparation method according to claim 1, characterized in that: The first organic solvent includes any one of dichloromethane, chloroform, acetone, butanone or 2-pentanone; The second organic solvent includes any one of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide or N,N-dimethylacetamide.
5. The preparation method according to claim 1, characterized in that: In the solution A, the concentration of polyvinylidene fluoride and hexafluoropropylene is 0.01-0.05 g / ml; In the solution B, the concentration of lithium polyetheretherketone sulfonate is 0.004-0.04 g / ml.
6. The preparation method according to claim 1, characterized in that: In step S2, the heating temperature is 25-60°C; the vacuum drying temperature is 25-100°C.
7. The preparation method according to claim 1, characterized in that: The solute of the electrolyte is bis(trifluoromethanesulfonyl)imide lithium salt, and the solvent is a mixed solvent of 1,3-dioxolane and ethylene glycol dimethyl ether; The concentration of the electrolyte is 0.8-2 mol / L.
8. A composite gel electrolyte prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the composite gel electrolyte according to claim 8 in a lithium battery.
10. A lithium battery, characterized in that: Comprising a positive electrode, a negative electrode and the composite gel electrolyte according to claim 8; The active material of the positive electrode includes any one of lithium iron phosphate and sulfur-carbon composite material, and the active material of the negative electrode includes lithium metal or lithium alloy.